Personality and phobias in adolescence: age and gender in psychopathological expressions - Salvatore Settineri; Emanuele Maria Merlo; Angela Alibrandi; Federica Sicari; Irene Pagano Dritto; Fiorella Strangis; Fabio Frisone (Journal of Mind and Medical Sciences)
Background: Although the understanding of adolescent phobias is important, this phenomenon has thus far not been adequately researched. This report, based on clinical experience, highlights prevalent phobic phenomena linked to personality characteristics. Methods: A sample of 241 adolescents from High School and the University of Messina, Italy was evaluated for phobic responses using the SAFA Scales. Personality types and aspects were assessed by the Myers-Briggs Type Indicator F Form. Results: The results were consistent with the reported literature and revealed that psychopathological phenomena such as anxiety, obsession, eating disorders and phobias decreased with aging; however, depression remained constant over time. Significant differences emerged regarding gender, with the presence of higher scores on all scales except obsession for the female group. Personality analysis revealed aspects linked to the relations between psychopathological variables, introversion/ extraversion (such as polar dimensions), and rational/ irrational functions. Conclusion: This research indicates that phobic phenomena may be underestimated in adolescents and links personality types and symptoms with phobic phenomena, indicating the potential need for interventions in adolescents.